The Treatment Of Impacted Maxıllary Canınes Hıgh In The Vestıbule - İlken Kocadereli; Ayhan Enacar (Galenos Yayinevi, 1993)
The combined surgical - orthodontic treatment of buccally impacted maxillary canines by a surgical procedure which was aimed to suture the flap high in the vestibule over the teeth is described. This method of surgical exposure protects attached gingiva and a future mucogingival defect can be avoided.